Inovasi Layanan Call Center 119 Kesehatan Di Indonesia: Problem Kesiapan Aparat - Taufiqurokhman; Mam’un Murod; Evi Satispi; Andriansyah Andriansyah; Lira Agusinta (Research and Development Agency Ministry of Home Affairs, 2022)
This study aims to describe and analyze health service innovations at the Ministry of Health of the Republic of Indonesia in the readiness of the apparatus to serve patients affected by the covid 19 virus. Call center 119 health services are medical emergency services that provide ambulance facilities and the need for a referral hospital for inpatients affected by COVID-19. This study uses the New Public Management (NPM) theory developed by Osborne and Gaebler (1992), which is an improvement from the Old Public Administration marked by the emergence of the concept of managerialism and the need for a new model in public service administration. The benefits of the research are expected to provide constructive input to the Ministry of Health of the Republic of Indonesia, which has made breakthroughs in health services. So that health services are of higher quality by applying the principles of excellent and fast service. The 119 call center service places trained and profesional operators, nurses, and doctors. The research methodology uses qualitative-descriptive, interactive models, creating interactive, deductive situations to obtain accurate data. Primary data sources were taken directly in the field based on interviews with the head of the human resource education center at the Indonesian Ministry of Health, the head of the Covid-19 task force at the athlete’s house, operators, nurses, doctors assigned by the DKI Jakarta Regional Government Health Office. The results show that the call center 119 public health service is a breakthrough in public health services, integrated emergency services, and the speed of medical service actions that can increase the degree and acceptability of health for the community. This public health service is integrated between inpatient home athletes and inpatient hospitals for COVID-19 patients by involving operator officers, nurses, trained and profesional doctors with the assistance of the Indonesian National Army (TNI) and the Indonesian National Police.